Meta-analysis and systematic review of the impact of different exercise intervention on emotional symptoms in patients with bipolar affective disorders - Fan, Dandan; Deng, Fangquan; Ji, Yin; Kong, Haijun; Zhang, Linjie; Fu, Yebiao; Zhang, Hanqiao; Zhang, Junting; Deng, Shiquan (Frontiers in Psychology, 2026)
ObjectiveThis study systematically evaluates the effects of diverse exercise and combined interventions on patients with bipolar disorder (BD), identifies optimal intervention parameters through subgroup analyses, explores dose–response relationships, and delivers evidence-based support for exercise interventions in this population.MethodsRandomized controlled trials (RCTs) examining exercise interventions for BD patients were retrieved from domestic and international databases. Literature screening and data extraction adhered to standard criteria. Study quality was assessed via the Cochrane Risk of Bias Tool 2.0. Meta-analyses were conducted in RevMan 5.4, while subgroup analyses (stratified by intervention type, duration, frequency, and age) and dose-response analyses were performed in Stata 15. The Benjamini-Hochberg method was used to apply false discovery rate (FDR) correction, controlling false positive risks in multiple comparisons (statistical significance was defined as corrected P < 0.05).ResultsExercise interventions significantly improved depression, anxiety, and mania symptoms and health questionnaire outcomes in BD patients (all corrected P < 0.05). No significant improvements were observed in quality of life questionnaire scores or systolic blood pressure (all corrected P > 0.05). For diastolic blood pressure, the pooled effect lacked statistical significance (SMD = −0.113, 95% CI: −0.665–0.439, P = 0.688), with only one individual study showing significant improvement after correction (corrected P = 0.0224). Subgroup analyses revealed the following: Exercise combined with psychological or mindfulness training improved all three symptoms (depression, anxiety, mania; all corrected P < 0.05), whereas exercise alone improved only mania (corrected P < 0.05). Interventions lasting ≤ 12 and >12 weeks both improved depression, anxiety, and mania (all corrected P < 0.05). Exercise performed ≤ 2 sessions/week improved only anxiety (corrected P < 0.05), while >2 sessions/week improved only depression and mania (all corrected P < 0.05). Single sessions lasting ≤ 60 and >60 min both improved mania (all corrected P < 0.05), but only sessions >60 min improved anxiety (corrected P < 0.05). Patients aged ≤ 40 and >40 years both derived benefits (all corrected P < 0.05). Dose-response analyses indicated that anxiety and depression scores were lowest with two exercise sessions per week (P < 0.01).ConclusionExercise interventions significantly improve depression, anxiety, and mania symptoms as well as health questionnaire outcomes in BD patients, with exercise combined with psychotherapy or mindfulness training producing superior effects. Improvements in diastolic blood pressure warrant cautious interpretation, as they are supported by only one study. The recommended protocol consists of exercise combined with psychotherapy or mindfulness training, with a duration of ≥12 weeks, 2–3 sessions/week, and single-session length ≤ 90 min; this protocol exerts a positive impact on patients' emotional symptoms. Future RCTs with larger samples and longer follow-up periods are needed to further validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251032877, identifier: CRD420251032877.